Upaya Peningkatan Literasi Sains Siswa Siswi SMPN 2 Narmada Melalui Pelatihan Jurnalistik Sejak Dini - Rudi Arrahman; Baiq Ruru Malani; Muhamad Alfin Tarmizi; Taufik Bahari; Nurita Ulfa; Maratin Konita (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
To This training service tries to solve the challenge of how students can read, watch, and write in a fun, pressure-free way, and are able to express their thoughts in the form of writing and content. The purpose of the Socialization is to provide an understanding to grade IX students about Efforts to Improve Science Literacy of SMPN 2 Narmada Students Through Early Journalism Training. This service activity was carried out at SMPN 2 Narmada, Sesaot Village, Narmada District, West Lombok Regency on Tuesday, September 12, 2023 which was attended by ninth grade students of SMPN 2 NARMADA totaling 90 people as the target of service with planning, implementation and evaluation methods. From the results of this service, students' knowledge before and after the socialization shows a difference, from the beginning the students did not know what Literacy and Journalism were, so it can be concluded that this socialization can be said to be successful because it has achieved its goals